Anti-hyperglycemic activity of encapsulated Java tea-based drink on malondialdehyde formation - Joncer Naibaho, Mega Safithri, Christofora Hanny Wijaya (Journal of Applied Pharmaceutical Science, 2019)
Nano-encapsulated Java tea-based beverage was previously reported capable of demonstrating the highest protective activity for Langerhans and beta-cell. The mechanism of anti-hyperglycemic activity, however, has remained unclear. This research aimed to study the mechanism of the beverage as an anti-hyperglycemic encapsulated functional drink through its role in malondialdehyde formation in streptozotocin-induced diabetic Sprague Dawley rats. The rats were divided into four groups: (A) normal rats as negative control, (B) untreated diabetic rats as positive control, (C) diabetic rats treated with micro-encapsulated drink (3.64 ml/200 g), and (D) diabetic rats treated with nano-encapsulated drink (3.64 ml/200 g). The intervention was conducted for 44 days. Malondialdehyde level was measured periodically every 2 weeks, body weight and blood glucose level were measured periodically every week for 6 weeks. Malondialdehyde level analysis in vitro was carried out as a comparison. Compared to malondialdehyde (MDA) level on positive control group, encapsulated Java tea-based beverages intervention attenuated the formation of malondialdehyde in diabetic rats from 36.63% to 51.95%. In addition, micro- and nano-encapsulated drink suppressed the fluctuation of blood glucose level and body weight. In vitro assessment showed that micro- and nano-encapsulated drink suppressed the formation of MDA at 5.25% and 72.16%, respectively. The anti-hyperglycemic activity of micro- and nano-encapsulated drink is shown by their ability to alleviate the MDA formation both in vivo and in vitro assessment.
Keywords: Diabetes mellitus, Java-tea based drink, micro-encapsulation, nano-encapsulation, lipid peroxidation.